(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Sino-nasal carcinoma has various histological types presented with different stages. Objectives: The purpose of this present study was to see the histopathological types and stages of sinonasal carcinoma patients in tertiary level hospital. Methodology: This cross-sectional study was conducted in the Department of Otolaryngology- Head & Neck Surgery at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh and Dhaka Medical College Hospital, Dhaka, Bangladesh from January 2008 to December 2009 for a period of two (02) years.All consecutive cases of sinonasal carcinoma admitted in hospital and outpatient department during the study period. Suspected cases of sinonasal carcinoma was diagnosed from history and clinical examination proved by CT-scan, MRI and histopathological examination. Result: A total number of 40 cases of sino-nasal carcinoma were recruited for this study. Among these single site involvement was reported in 11 cases and the rest 29 cases were involved in multiple sites. Regarding multiple sites involvement maxillary sinus with nasal cavity involvement was reported in 15(51.72%) cases. Maxillary sinus, nasal cavity with ethmoid sinus involvement was found in 10(34.48%) cases. The presentation of the sinonasal carcinoma at stage T4 was 16(40.05) cases followed by T3, T2, and T1 which were 13(32.5%) cases, 7(17.5%) cases and 4(10.0%) cases respectively. Squamous cell carcinoma was found in 25(63%) cases followed by adenocarcinoma andadenoid cyst carcinoma which were 7 cases, 5 cases respectively. Conclusion: In conclusion majority of the sino-nasal carcinoma are squamous cell carcinoma involving the multiple sites in the T4 stage. Journal of National Institute of Neurosciences Bangladesh, 2020;6(2): 110-113